Comparative Evaluation of the Effect of Diode Laser Irradiation, Fluoride Varnish, and Casein Phosphopeptide-Calcium Amorphous Phosphate on Demineralized Enamel Microhardness - Mohammad Hossein Nosrati; Mahshid Saffarpour; Atefeh Yousefi Jordehi (Mashhad University of Medical Sciences, 2022)
Introduction: Laser diode irradiation, the use of fluoride varnish, and casein phosphopeptide-calcium amorphous phosphate (CCP-ACP) paste have been suggested as effective methods to increase the enamel resistance to decay. The present study aimed to investigate the effect of fluoride varnish, CPP-ACP paste, and diode laser radiation on the microhardness of demineralized enamel. Methods: In this experimental study, 78 extracted human premolar teeth were selected and sectioned into two buccal and lingual halves. The samples were immersed in demineralization solution, and primary micro-hardness was measured. Thereafter, the samples were randomly assigned to six groups: control group, 5% fluoride varnish, CPP-ACP paste, diode laser (2W, 940nm) for 40 sec, laser combined with fluoride varnish, and CPP-ACP paste in combination with laser. The microhardness of the samples was measured again after different treatments. Data were analyzed in SPPS software (version 23) using repeated measures analysis of variance (RM ANOVA) (P<0.05). Results: There was no significant difference in the microhardness values among different groups (P<0.05). The comparison of the mean microhardness between before and after treatment for each group revealed a significant difference in the enamel microhardness only in the CPP-ACP paste (P=0.003) and diode laser (P=0.009) groups. Conclusion: As evidenced by the results of this study, the use of fluoride varnish, CPP-ACP paste, and diode laser radiation did not increase the microhardness and remineralization of tooth enamel. Moreover, laser diode irradiation with the parameters used in this study does not enhance the remineralization effect of fluoride varnish and CPP-ACP paste.